Copper‐Catalyzed Oxidative Dehydrogenative C(sp3)−H Bond Amination of (Cyclo)Alkanes using NH‐Heterocycles as Amine Sources. Issue 15 (10th July 2017) - Wang, Chang‐Sheng; Wu, Xiao‐Feng; Dixneuf, Pierre H.; Soulé, Jean‐François
Abstract: A copper‐catalyzed oxidative C(sp 3 )−H/N−H coupling of NH‐heterocycles with affordable (cyclo)alkanes has been developed. This procedure involves C(sp 3 )−N bond formation through a radical pathway generated by homolytic cleavage of di‐ tert ‐butyl peroxide and trapping of the radical(s) by copper catalysts. The reaction tolerates a series of functional groups, such as bromo, fluoro, ester, ketone, nitrile, methyl, and methoxy. free‐NH‐containing indoles, pyrroles, pyrazoles, indazoles, and benzotriazoles are successfully N ‐alkylated. Abstract : Outstanding achievement in amination : A variety of N ‐alkylated heterocycles is facilely synthesized by direct C−H bond amination of low‐cost (cyclo)alkanes catalyzed by inexpensive copper salts. A wide range of NH‐heterocycles are used as amine sources and the reaction displays good functional group compatibility.